AVALIAÇÃO DA ADOÇÃO DAS MEDIDAS DE PRECAUÇÕES PADRÃO EM CATEGORIAS ESPECÍFICAS DE PROFISSIONAIS DE SAÚDE - Ana L. N. Junqueira; Sheila A. Teles; Maria A. Barbosa; Tatiane M. Pereira; Kézia F. Castro; Tatiana O. Santos; Marinésia A. Prado (Universidade Federal de Goias, 1999)
A survey of health care workers who were thought likely have frequent and intensive exposures to blood and other body fluids, anaesthetists, was carried out to asses the frequency of self-reported occupational exposures to blood and other body fluids, the knowledge and the compliance with regard standard precautions. Of all interviewed profissionals, 62.8% reported occupational exposures to blood and/or other body fluids by percutaneous injuries and/or mucous membranes contacts. All profissionals reported knowledge about standard precautions and the most of them assumed the use of these precautions, and hepatitis B vaccination. Nevertheless was observed a poor adherence to standard precautions in their practices, principally, concerning the use of masks, protective eyeglasses and handwashings. This study emphasizes the importance of developing new strategies for precautions standards training.